Letter to John T. Tucker from Clyde W. Page Jr. - Clyde W. Page Jr.:::::: (1971)
A letter to John T. Tucker from the Acting Director of Airport Services Clyde W. Page, Jr. informing him that if the property of the former Oxnard Air Force Base is handed over to the local government, then it is up to them to decide how to proceed.